A rare clinical presentation of dermatitis herpetiformis with blisters principally on elbows: a report of three female cases - Magdalena Jałowska; Bogusz Falkowski; Maciej Spałek; Michał Owczarek; Justyna Gornowicz-Porowska; Monika Bowszyc-Dmochowska; Maria Raptis-Bolwach; Marian Dmochowski (Przegląd Dermatologiczny)
According to our experience, dermatitis herpetiformis usually occurs in young males who present with an itchy polymorphic eruption, without blisters or even overt vesicles, localized symmetrically on elbows, 1/3 of the proximal part of extensor surfaces of forearms, buttocks and knees. To raise awareness among practitioners of the diversity of clinical phenotypes of dermatitis herpetiformis in this article we describe three females with a rare clinical presentation of dermatitis herpetiformis characterized by blisters right on the elbows. Such a presentation can mimic epidermolysis bullosa acquisita. The appearance of blisters may be due to ageing of the skin in the elderly, abrupt discontinuation of dapsone therapy, or implementation of drugs that exacerbate the disease. Female gender influences cannot be excluded.